Are body roundness index and a body shape index in the first trimester related to foetal macrosomia?. (3rd April 2022) - Ozler, Sibel; Kozanhan, Betul; Bardak, Omer; Arıkan, Mehmet Nurullah
Abstract: This study investigated the effectiveness of maternal Body Roundness Index (BRI), Body Shape Index (ASBI), and Visceral Adiposity Index (VAI) in predicting foetal macrosomia and small for gestational age (SFGA) babies in obese and non-obese pregnant women. This prospective trial included 168 pregnant women (99 obese and 69 non-obese). A logistic regression model was used to identify the independent risk factors of foetal macrosomia and SFGA. BRI, waist/hip ratio, HbA1c and HOMA-IR were found to be significantly associated with increased macrosomia risk in obese women (OR = 1.469, % CI: 1.126–1.917, p = .005; OR = 4.289, % CI: 0.178–1.030, p = .012, OR = 6.277, %Cl: 1.233–31.948, p = .027, and OR = 1.393, %Cl: 1.060–1.832, p = .017). The present study indicates that first-trimester BRI and waist/hip ratio may be powerful determinants in predicting foetal macrosomia in obese pregnant women. Impact statement: What is already known on this subject? Obesity is a major risk factor for maternal and foetal morbidity and mortality. The rate of obesity continues to increase rapidly around the world. The accuracy of ultrasound in estimated foetal weight is reduced in obese pregnant women. The Body Roundness Index (BRI) is a new anthropometric index that shows body fat distribution. What do the results of this study add? Our results show that the BRI was an independent risk factor associated with foetal macrosomia in obese pregnant women. What are the implications of these findings for future clinical practice and/or further research? BRI measurements should be taken before pregnancy to help predict shoulder dystocia, GDM, FGR and foetal macrosomia in obese women.